The Concept of Media (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article is devoted to the legal analysis of the legal consequences of unreasonable interference in journalistic activities. The article pointed out that prior to this period, no law was passed regulating social attitudes related to unreasonable interference in journalistic activities. It is justified that this social attitude cannot be regulated through the analogy of law and law.